Amazing Animal Disguises - Sowler, Sandie; Nang Chan Yeema (New York, United States Alfred A. Knopf, 1992)
Introduces animal disguises involving camouflage and mimicry, in such animals as the zebra, polar bear, and caterpillar.
Keywords: Juvenile Nonfiction